The study on income generation strategy: the case of Suruhanjaya Syarikat Malaysia Muar / M Effendy Abdullah Azillah - Azillah, M Effendy Abdullah (Faculty of Business and Management, 2009)
A business (also called a company, firm and enterprise) is a legally recognized organization designed to provide goods and/or services to consumers (Steven M. Sheffrin ; Wikipedia). Businesses are predominant in capitalist economies, most being privately owned and formed to earn profit that will increase the wealth of its owners and grow the business itself. The owners and operators of a business have as one of their main objectives the receipt or generation of a financial return in exchange for work and acceptance of risk. Notable exceptions include cooperative enterprises and state-owned enterprises. Socialist systems involve government agencies, public ownership, stateownership or direct worker ownership of enterprises and assets that would be run as businesses in a capitalist economy. The distinction between these institutions and a business is that socialist institutions often have alternative or additional goals aside from maximizing or turning a profit. (Wikipedia) The word "business" relates to the state of being busy either as an individual or society as a whole, doing commercially viable and profitable work. The term "business" has at least three usages, depending on the scope. The singular usage (above) to mean a particular company or corporation, the generalized usage to refer to a particular market sector, such as "the music business" and compound forms such as agribusiness, or the broadest meaning to include all activity by the community of suppliers of goods and services. However, the exact definition of business, like much else in the philosophy of business, is a matter of debate. Companies Commission of Malaysia or SSM is form purposely to serve as an agency to incorporate companies and register businesses in Malaysia. It means to ensure the incorporation and business registration activities runs accordance to government compliance. SSM also monitor all corporate and business activities to build and maintain positive development through comprehensive enforcement.